EVALUATION USAGE OF ANTIBIOTIC TO SEPSIS NEONATUS PATIENT IN RSUD ARIFIN ACHMAD PROVINCE RIAU - Rizki Giofani; Nazardi Oyong; Inayah " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTSepsis neonatus is systemic clinical syndrome usually accompanied withbacteremia that needed prompt and proper antibiotic therapy. This study purposewas evaluating usage of antibiotic to sepsis neonatus patient in RSUD Arifin AchmadProvince Riau. This study method was descriptive retrospective. Data sources weretaken from medical record of sepsis neonatus patient in RSUD Arifin AchmadProvince Riau period 1 January - 31 December 2015. Based on characteristic ofpatient, neonatal sepsis mostly found on female 57,4%, low birth weight 57,8%, lowgestational age 66,2%, and pervaginum labor 52,9%. Blood culture time, found thatmost culture more than 3 days 63,2%. Microorganism of cause mostly foundCoagulase Negative Staphylococci 35,3%. Usage of empirical antibiotics mostlygiven 2 antibiotics 60,3%, type of antibiotic was aminoglycoside 42,1%, withduration more than 72 hours 55,5%. Usage of definitive antibiotics mostly were notgiven to sepsis neonatus patient 44,1%, while mostly they were given single antibiotic30,9%, most used type of antibiotic were aminoglycoside 40% (20 of 60 antibiotics),and duration less than 7 days 50% (30 of 60 antibiotics). Conclusion of this studywere duration of empiric antibiotics mostly given combination of two antibiotics withduration more than 72 hours and empiric antibiotics were suitable withmicroorganism that caused sepsis in RSUD Arifin Achmad 2015.Key word : sepsis neonatus, empiric antibiotic, definitive antibiotic